The Ethics and Procedures of Financial and Sustainability Reporting: Accounting Students' Perceptions - Chelsya Chelsya; Emillia Sastrasasmita; Arifuddin Arifuddin; Asri Usman (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines accounting students' perceptions of the ethics and procedures of financial reporting and sustainability reporting, and tests whether these perceptions differ between lower-level and upper-level students. Research Method: A descriptive quantitative survey was conducted using cluster sampling. A questionnaire grouped items into five categories: misstatement, disclosure, cost and benefit, accountability, and the usefulness of sustainability reporting. Responses from 166 students, split into lower-level and upper-level groups, were analyzed using descriptive statistics, Levene's homogeneity test, and the Mann–Whitney U test. Results and Discussion: All five hypotheses were rejected (Asymp. Sig. (2-tailed) ranging from 0.105 to 0.928, all > 0.05), indicating no significant differences in perception between the two groups across the five categories tested. Implications: The findings suggest that semester level does not produce a significant difference in students' perceptions of financial reporting and sustainability reporting ethics, which may inform how accounting ethics is sequenced in the curriculum. Originality: This study jointly assesses perceptions of financial reporting ethics and sustainability reporting across student levels within a single instrument.